Calculation of response functions for cylindrical nested neutron spectrometer - Chu, Vu Long; Nguyen, Huu Quyet; Nguyen, Ngoc Quynh; Le, Ngoc Thiem (Nuclear Science and Technology, 2017)
In a recent work, a new neutron spectrometer, namely Cylindrical Nested Neutron Spectrometer (CNNS). It works under the same principles as a Bonner Sphere Spectrometer (BSS), except that different amounts of moderator around a thermal neutron detector are configured by adding or removing cylindrical shells. The CNNS consists of a 4mm x 4mm 6LiI(Eu) scintillator crystal and nested cylindrical polyethylene moderators. The objective of this paper is describing the use of MCNPX code for determining a optimal ratio between height and diameter of the moderators in order to remain isotropic angular response to neutrons like BSS and determining of response functions for moderators of different diameters at 104 energy points from 0.001 eV to 19.95 MeV.